Ekstraksi Pigmen Karotenoid dari Buah Pepaya (Carica papaya L.) dan Aplikasinya Sebagai Pewarna Pangan Alami Nasi Instan Melalui Teknologi Mikroenkapsulasi - hidayat, umar (Indonesian Journal of Nutrition Science and Food, 2023)
The aim of this research was to optimize extraction carotenoids from papaya fruit and apply it as food colouring for instant rice. The extract was processed by microencapsulation and the microcapsules were used as natural colouring of instant rice. The study was designed as completely randomized designed with 3 x 2 factorial pattern. This study was divided into three parts. The first part was sample preparation and extraction process. The second part was manufacture of carotenoids microcapsules and instant rice. The third part was analyzed of product i.e total content of carotenoid extract, water content test, carotenoids stability test, color intensity test, and rehydration time test. The data was analyzed by One Way ANOVA with SPSS 16.0 software at significance level of p <0.05. The result showed that : a) the selected extraction method which produce optimal results was extraction by acetone-hexane at 35 °C, b) there was a significant effect of sun exposure to the stability of the total carotenoid content of microcapsule, c) the total carotenoid content of papaya fruit extract in acetone-hexane was 4833.3 mg / 100 g, d) the highest total carotenoid levels of microcapsule was indicated by A samples 111.807 mg / 100g , e) the highest total carotenoid content of instant rice was 23.6592 mg / 100g, and f) the average of rehydration time all of instant rice samples were less than 2 minutes. g) the microcapsules had water content 4.80%, h) the instant rice colour values were L = 98,33 – 98,83; a = (-0,33) – (-0,44667); and b = (+6,42333) – (+6,52333). It can be concluded that microencapsulation can be used as one method to develop pigment-based natural ingredients such as papaya fruit that can be used for food, but research and development are needed to improve the resulting microcapsules product.